Dietary factors and diabetes-related health outcomes in patients with type 2 diabetes: protocol for a systematic review and meta-analysis of prospective observational studies - Lukas Schwingshackl; Sabrina Schlesinger; Janett Barbaresko (BMJ Open)
Introduction Type 2 diabetes (T2D) is a major health concern associated with several comorbidities such as diabetic chronic kidney disease, neuropathy and cardiovascular diseases. Many of these complications may be preventable by an adequate lifestyle, including a favourable dietary behaviour, additionally to pharmacological management. In general, dietary guidelines for patients with diabetes recommend a hypocaloric diet to achieve a normal weight, but there is a lack of detailed instructions on specific nutrients and foods to prevent diabetes-related outcomes. Therefore, the aim of this systematic review and meta-analysis is to summarise the available evidence on the association between dietary factors and health-related outcomes in patients with T2D.Methods and analysis A systematic literature search will be conducted in PubMed and Web of Science in May 2019 to identify prospective observational studies investigating dietary factors in association with major complications in patients with T2D. We will include studies investigating dietary patterns, food groups, foods, macronutrients and micronutrients as well as secondary plant compounds. As diabetes-related outcomes, we will include macrovascular (cardiovascular and cerebrovascular diseases) and microvascular outcomes (nephropathy, neuropathy and retinopathy), as well as cancer, quality of life, depression, cognitive disorders and mortality. We will conduct dose-response meta-analyses using random effects models. We will investigate heterogeneity across studies and publication bias. To assess the risk of bias and quality of the included studies, we will use the Cochrane risk of bias tool ROBINS-I and the quality of evidence will be assessed using Grades of Recommendation, Assessment, Development, and Evaluation.Ethics and dissemination As the systematic review is based on published studies, ethical considerations are not required. The systematic review and meta-analysis will be published in a peer-reviewed Journal.PROSPERO registration number CRD42018110669